2015
DOI: 10.1111/1755-5922.12160
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Vascular Imaging in Guiding Routine Percutaneous Coronary Interventions: A Meta‐Analysis of Bare Metal Stent and Drug‐Eluting Stent Trials

Abstract: SUMMARYBackground: The routine use of vascular imaging including intravascular ultrasound (IVUS) and optical coherence tomography (OCT) in guiding percutaneous coronary interventions (PCI) is still controversial especially when using drug-eluting stents. A meta-analysis of trials using bare metal stents was previously published. Methods: We conducted a meta-analysis of available published trials that compared imaging-guided PCI and angiography-guided PCI in patients undergoing routine PCI only. Trials that enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 31 publications
(11 reference statements)
0
10
0
2
Order By: Relevance
“…Therefore, these intravascular modalities have been widely used in contemporary PCI era. However, in large‐scale multicenter studies for patients with acute myocardial infarction (AMI), few data are available for current patterns of use of intravascular modality such as IVUS, OCT, and FFR . Moreover, patient and procedural‐based outcomes related to intravascular modality guidance compared to angiography guidance have not been fully investigated yet.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, these intravascular modalities have been widely used in contemporary PCI era. However, in large‐scale multicenter studies for patients with acute myocardial infarction (AMI), few data are available for current patterns of use of intravascular modality such as IVUS, OCT, and FFR . Moreover, patient and procedural‐based outcomes related to intravascular modality guidance compared to angiography guidance have not been fully investigated yet.…”
Section: Introductionmentioning
confidence: 99%
“…At present, clinical imaging such as coronary angiography, intravascular ultrasonography, and optical coherence tomography are expensive and invasive, which could also produce some certain complications like thrombosis formation, infection, and coronary artery dissection . The other imaging methods including coronary computed tomography angiography and magnetic resonance imaging (MRI) usually put much more emphasis on the internal structure of the vessel or the extend of luminal stenosis anatomically, so that the composition within the lesion which play a vital role in the progression of atherosclerosis plaques is ignored .…”
Section: Introductionmentioning
confidence: 99%
“…Several meta-analyses which have included randomized trials, registries, and observational studies have been published on the role of IVUS during PCI with BMS and DES 16, 17, 19, 20, 21, 25, 26, 27, 28, 29. The most recent of these meta-analyses by Steinvil et al concluded that IVUS-guided PCI was associated with better overall clinical outcomes than angiography-guided DES implantation.…”
Section: Introductionmentioning
confidence: 99%